Movement, knowledge, emotion : gay activism and HIV/AIDS in Australia - Power, Jennifer (Australian National University E Press, 2011)
"This book is about community activism around HIV/AIDS in Australia. It looks at the role that the gay community played in the social, medical and political response to the virus. Drawing conclusions about the cultural impact of social movements, the author argues that AIDS activism contributed to improving social attitudes towards gay men and lesbians in Australia, while also challenging some entrenched cultural patterns of the Australian medical system, allowing greater scope for non-medical intervention into the domain of health and illness. The book documents an important chapter in the history of public health in Australia and explores how HIV/AIDS came to be a defining issue in the history of gay and lesbian rights in Australia"--Publisher's description